2024
DOI: 10.21037/gs-23-480
|View full text |Cite
|
Sign up to set email alerts
|

Seeding recurrence of follicular thyroid carcinoma after transoral endoscopic thyroidectomy vestibular approach: a case report

Moon Young Oh,
So Won Oh,
Young A Kim
et al.

Abstract: Background While track recurrence of thyroid cancer following endoscopic and robotic transaxillary surgeries has been reported previously, no such cases have been reported for transoral endoscopic thyroidectomy vestibular approach (TOETVA). This case report describes the first documented case of recurrence of thyroid cancer along the surgical track after TOETVA. Case Description The patient underwent right lobectomy via TOETVA for a 4 cm follicular thyroid carcinoma (FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In cases of malignancy, we observed that the tissue tends to be notably firm and dense, making it challenging to extract the specimen through a smaller vestibular incision. Moreover, there is a concerning risk of tumor spillage below the jaw, potentially necessitating subsequent major surgery ( 23 , 26 ). To mitigate these risks, we adhered strictly to the findings of prior studies, which indicated that nodules smaller than 20 mm could be safely removed from a vestibular incision without causing mental nerve injury or specimen fracture, achieving a specificity rate of 100% ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cases of malignancy, we observed that the tissue tends to be notably firm and dense, making it challenging to extract the specimen through a smaller vestibular incision. Moreover, there is a concerning risk of tumor spillage below the jaw, potentially necessitating subsequent major surgery ( 23 , 26 ). To mitigate these risks, we adhered strictly to the findings of prior studies, which indicated that nodules smaller than 20 mm could be safely removed from a vestibular incision without causing mental nerve injury or specimen fracture, achieving a specificity rate of 100% ( 27 ).…”
Section: Discussionmentioning
confidence: 99%